Frequency of Thrombocytopenia in Pregnant Females - Saima Qurban, Sanniya Arshad, Samar Hussain, Sajida Imran, Asima Munawar, Muhammad Naim Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was aimed to assess the frequency of thrombocytopenia in pregnant females. Study design: Descriptive cross-sectional study Place and duration of study: Rashid Latif Medical College, Lahore, From November, 2021 to April, 2022. Methods: A total of 380 pregnant females were enrolled to examine. Blood samples from pregnant women were taken to measure the platelet counts by using hematology analyzer. For statistical significance, proportions were analyzed with the Chi square. Detailed socio-demographics of enrolled cases included age, residence, occupational status, educational status, reproductive and related characteristics and BMI were recorded after taking informed written consent. SPSS-21was used to analyze the data. Results: In this study, 380 pregnant females were included with mean age 28.1years. Majority of the females 228/380 (60%) had rural residence, 160 (42.1%) were in third trimester of their pregnancy. Frequency of thrombocytopenia was recorded in 40 pregnant females as 10.5%. Females in their third trimester had moderate thrombocytopenia of about 81.0%, in second trimester 76.0% and in first trimester 74.0% respectively. Conclusion: Thrombocytopenia is a frequent complication of pregnancy. In the third trimester of pregnancy, thrombocytopenia was shown to affect a disproportionately high number of the women. Most patients are asymptomatic, hence it is important to assess for it by checking the peripheral smear and platelet count often throughout pregnancy, especially in the third trimester. Keywords: Thrombocytopenia, pregnant females, third trimester.